Reflection and perspective on international workplace learning research: A literature review - Yifan Zhao (Adult Education Research Conference, 2020)
In recent years, researchers' interest in workplace learning has increased dramatically. Many journals show the current research status of workplace learning. This study uses bibliometrics, cluster analysis, knowledge map to analyze 1764 literatures in 8 journals of workplace learning in 2010-2019. Research findings: (1) The research topics of workplace learning are relatively micro and diverse. Workplace learning theory, influencing factors of workplace learning, workplace learning evaluation, leadership, performance improvement and organizational change are the current research hotspot. (2) Empirical research is the majority research method. (3) Workplace learning theoretical model, informal learning, performance improvement, organizational learning, innovation, leadership are the future research trends.
Keywords: workplace learning; research hotspot; research reflection; research prospect